A mixed-method analysis of the role of online communication attitudes in the relationship between self-monitoring and emerging adult text intensity. (December 2018) - Dorrance Hall, Elizabeth; Kenny Feister, Megan; Tikkanen, Stephanie
Abstract: Text messaging is increasingly central in the lives of emerging adults in the United States, yet compulsive texting is related to poor grades, lack of school bonding, and lower perceived scholastic competence. This mixed-method study aimed to discover whether online communication attitudes (OCA) mediate the relationship between self-monitoring, the trait-like propensity for awareness and adaptation to social situations, and text intensity, a behavioral indicator of the centrality of texting in one's life. A mediation model was tested utilizing survey data from 414 college students from the Midwestern and Western U.S. At the zero-order level, all five OCA were associated with text-intensity. In the mediational model, high self-monitoring was associated with less text intensity, except when participants endorsed attitudes that texting facilitates social connection and they did not feel apprehensive about texting. The indirect effect of self-monitoring on text intensity through those attitudes was positive. Theoretical implications for technologically mediated communication (TMC) scholarship and the impression management model (IMM) are discussed. Highlights: At the zero-order level, all five OCA were associated with text-intensity. At the zero-order level, all five OCA were associated with self-monitoring. Self-monitoring on text intensity was mediated by social connection and apprehension. Self-monitoring was associated with less text intensity when OCA were in the model.